Selective ischemic-hemisphere targeting Ginkgolide B liposomes with improved solubility and therapeutic efficacy for cerebral ischemia-reperfusion injury - Yang Li; Miaomiao Zhang; Shiyi Li; Longlong Zhang; Jisu Kim; Qiujun Qiu; Weigen Lu; Jianxin Wang (Asian Journal of Pharmaceutical Sciences, 2023)
Cerebral ischemia-reperfusion injury (CI/RI) remains the main cause of disability and death in stroke patients due to lack of effective therapeutic strategies. One of the main issues related to CI/RI treatment is the presence of the blood-brain barrier (BBB), which affects the intracerebral delivery of drugs. Ginkgolide B (GB), a major bioactive component in commercially available products of Ginkgo biloba, has been shown significance in CI/RI treatment by regulating inflammatory pathways, oxidative damage, and metabolic disturbance, and seems to be a candidate for stroke recovery. However, limited by its poor hydrophilicity and lipophilicity, the development of GB preparations with good solubility, stability, and the ability to cross the BBB remains a challenge. Herein, we propose a combinatorial strategy by conjugating GB with highly lipophilic docosahexaenoic acid (DHA) to obtain a covalent complex GB-DHA, which can not only enhance the pharmacological effect of GB, but can also be encapsulated in liposomes stably. The amount of finally constructed Lipo@GB-DHA targeting to ischemic hemisphere was validated 2.2 times that of free solution in middle cerebral artery occlusion (MCAO) rats. Compared to the marketed ginkgolide injection, Lipo@GB-DHA significantly reduced infarct volume with better neurobehavioral recovery in MCAO rats after being intravenously administered both at 2 h and 6 h post-reperfusion. Low levels of reactive oxygen species (ROS) and high neuron survival in vitro was maintained via Lipo@GB-DHA treatment, while microglia in the ischemic brain were polarized from the pro-inflammatory M1 phenotype to the tissue-repairing M2 phenotype, which modulate neuroinflammatory and angiogenesis. In addition, Lipo@GB-DHA inhibited neuronal apoptosis via regulating the apoptotic pathway and maintained homeostasis by activating the autophagy pathway. Thus, transforming GB into a lipophilic complex and loading it into liposomes provides a promising nanomedicine strategy with excellent CI/RI therapeutic efficacy and industrialization prospects.